MENINGKATKAN KEMAMPUAN BERTANYA SISWA MELALUI LAYANAN BIMBINGAN KELOMPOK DI KELAS VII-3 SMP NEGERI 29 MEDAN PADA TAHUN PELAJARAN 2016-2017 - Lertina Pakpahan (Universitas Islam Negeri Sumatera Utara Medan, 2019)
Lertina Pakpahan. The improving of stuents’ competence in asking through group guidence service at VII-3 grade SMP Negeri 29 Medan in 2016/2017 academic year. The aim of this study is to improve stuents’ competence in asking through grouping guidence service at VII-3 grade SMP Negeri 29 Medan in 2016/2017 academic year. The method used in this study is classroom action research with three cycles. The sunjects of this study are 36 students. The technique in collecting data is test, qustioner and observation.The technique of analizing data in this study is descriptive comparation. It is because to compare the score both first and second cycles and to compare the students’ competence in grouping guidence service . In analyzing data gottten in this study, The researcher also conducts descriptive persentation analyzing data. The result of the study shows there is the improving of students’ involving in grouping guidence service, It is seen from new aspect understanding. The improving are in positif feeling, action plan, anthusiasm. These aspsecs can be observeb during the study. The improving can be seen in asking competence, the questiion is in spontanious, atending the situation in asking, atending the way of asking siuitable with the value and norm. There are nine indecators in asking competence which is observeb. The improving can be seen from the cycle I, II and III. In Cycle I, The average percentage is 45,52%, In The second cycle is 60% and the third cycle is 87,77%. The average level of improving in asking in first cycle is 45,51%, in the second cycle is to be 66,99% and the third cycle is improving to be 93, 32%.Key words: Asking competence, grouping guidence service